(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2020)
As blended and online learning grow less common education, instructors must rethink fundamental issues such as educating, learning, and assessment in unconventional settings. Such concerns include knowing how formative assessment works for online and blended learning, as well as the reliability and validity of evaluation in digital environments in regard to achieving the intended purposes. The purpose of this article is to provide a systematic qualitative review of the research literature on online formative assessment for higher education. One method used in this review was an integrative story review that includes methodical searching, reading, then writing of the literature to draw up major themes and findings of work in this topic. The authors used qualitative research criteria for choosing and examine the existing literature, focusing on examining and defining the core themes that are central to the concept of formative assessment, with a special emphasis on its implementation in online and blended settings. For summative assessment, students, peers, and instructors employed a range of tactics, many of which were connected to digital sites such as self-test quizzes, conversation forums, and e-portfolios. The advantages claimed include increased student participation and centrality within the process as important participants, as well as the formation of a learning society[1].